On Signs, Language, and Thought - Degutis, Algirdas (Problemos, 1984)
It is argued that the meaning of both natural and conventional signs is derivative from and dependent upon the linguistic meaning. Therefore, philosophical analysis of linguistic meaning cannot be based on the conceptual resources of semiotics but must be considered as a basis itself. It should also constitute the basis of a philosophical investigation of thought, since language and thought are functionally identical.